PENGARUH STRATEGI PEMASARAN MEDIA SOSIAL TERHADAP KEPERCAYAAN KONSUMEN DAN BRAND AWARENESS PADA PRODUK ES KRIM MOMOYO DI BALAI JAYA KOTA KABUPATEN ROKAN HILIR: strategi pemasaran, media sosial, kepercayaan konsumen, brand awareness - Rani Angelina; Aulia Indra (LPPM STIEM BONGAYA, 2026)
This study aims to analyze the effect of social media marketing strategy on consumer trust and brand awareness of Momoyo ice cream products in Balai Jaya Kota, Rokan Hilir Regency. A descriptive quantitative method was used with 100 respondents selected via the Slovin formula. Data were collected through a Likert-scale questionnaire and analyzed using t-tests, MANOVA, and coefficient of determination with SPSS 26. The results show that social media marketing strategy has a positive and significant effect on consumer trust (t = 9.112; sig. 0.000) and brand awareness (t = 9.377; sig. 0.000), and simultaneously affects both variables (Wilks' Lambda = 0.299; F = 6.565; sig. 0.000). Social media marketing explains 45.9% of the variation in consumer trust and 47.3% in brand awareness. It is concluded that optimal use of social media through online communities, interaction, content sharing, accessibility, and credibility effectively enhances consumer trust and brand awareness for Momoyo ice cream.